The Influence of the Effectiveness of the Audit Committee and Corporate Governance on the Prevention of Financial Crime in Manufacturing Companies in Indonesia - Suci Fadila (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This study aims to find out and analyze how much effect effectiveness and governance have on fraud in manufacturing companies in Indonesia. The type of data used is quantitative data sourced from financial statements and annual reports of manufacturing sector companies on the IDX. The analytical method used is panel data linear regression method. In this study the authors analyze how effective the audit committee and corporate governance are against fraud. The results of the study partially state that the effectiveness of the board of directors, audit committee size, independent directors, audit quality, leverage, and company size have a significant effect on corporate financial crimes. However, the effectiveness of audit committees, audit committees with accounting expertise, boards of directors with accounting expertise, board size, and independent risk committees had no effect on corporate financial crimes. Increasing the effectiveness of audit committees and corporate governance can have a positive impact on company quality. One way to increase the quality of a company is to create clean and fraud-free company financial reports through qualified human resources within the company. This research is expected to be able to contribute to knowledge in the field of corporate financial fraud prevention in Indonesia.